Accumulation of versican facilitates wound healing: Implication of its initial ADAMTS-cleavage site - Shamima Islam (2020)
© 2019 Elsevier B.V. Versican is a large chondroitin sulfate/dermatan sulfate proteoglycan in the extracellular matrix, and is expressed at high levels in tissues during development and remodeling in pathological conditions. Its core protein is cleaved at a region close to the N-terminal end of CSβ domain by several members of a disintegrin and metalloproteinase with thrombospondin motifs (ADAMTS) family, i.e., ADAMTS-1, 4, 5, 9, 15, and 20. Here, using a CRISPR/Cas9 system, we generated knock-in mice (V1R), which express an ADAMTS cleavage-resistant versican. Some V1R homozygote mice, termed R/R, exhibit syndactyly and organ hemorrhage. In wound healing experiments, R/R wound shows accumulation of versican and activated TGFβ-signaling in the early stage, leading to faster healing than wild type wound. Immunostaining for Ki67, CD31, smooth muscle α-actin, periostin demonstrates higher levels of overall cell proliferation and an increased number of endothelial cells and myofibroblasts. Immunostaining for CD11b and qRT-PCR for macrophage markers revealed increased levels of inflammatory cell infiltration, especially those of M1 macrophages. Cultured R/R dermal fibroblasts revealed increased deposition of versican, type I and III collagens, and hyaluronan, and upregulation of Smad2/3 signaling. Taken together, these results demonstrate that the cleavage site determines versican turnover and that versican plays a central role in the provisional matrix during the wound repair.